1989
DOI: 10.1007/bf02399667
|View full text |Cite
|
Sign up to set email alerts
|

Positive regulation of theDrosophila melanogaster G6PD gene by an insertion sequence

Abstract: In a previous study, we have shown that the three high-G6PD activity mutants are characterized by insertion of the Ins1 sequence consisting of a core sequence flanked by two defective P elements (KP and KP'; the 32nd base of the KP was replaced by guanine in the KP') in front of exonI of the G6PD gene and that the sequence responsible for positive regulation of the G6PD gene expression might be the core sequence but not the flanking KP and KP' elements. The core sequence is composed of either one or two identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Whereas much of the mobile sequence has decayed, the hormone-responsive enhancer has been conserved. An insect example involves a positive regulatory sequence of the D. melanogaster G6PD gene located within a composite set of P elements 5' to the coding region (Ito et al, 1989). SINEs, including Alu sequences or other pol III elements placed adjacent to coding regions can similarly promote transcriptional increase (Oliviero & Monaci, 1988).…”
Section: Transposable Elements As Gene Regulatory Sequencesmentioning
confidence: 99%
“…Whereas much of the mobile sequence has decayed, the hormone-responsive enhancer has been conserved. An insect example involves a positive regulatory sequence of the D. melanogaster G6PD gene located within a composite set of P elements 5' to the coding region (Ito et al, 1989). SINEs, including Alu sequences or other pol III elements placed adjacent to coding regions can similarly promote transcriptional increase (Oliviero & Monaci, 1988).…”
Section: Transposable Elements As Gene Regulatory Sequencesmentioning
confidence: 99%
“…Preference of the 5' noncoding regulatory region in the P insertion is also documented at other loci, yellow (Chia et al, 1986;Geyer et al, 1988), rudimentary (Tsubota et al, 1985;Tsubota and Schedl, 1986), RplI215 (Searles et al, 1986), suppressor of sable (Chang et al, 1986) and singed (Roiha et al, 1988). Although it is not known if the same holds at the G6PD locus, our previous (Ito et al, 1989) and present studies demonstrated that the site of P-element insertion is located in the 5' region of the G6PD gene similarly in the three high-G6PD-activity mutants.…”
Section: Discussionmentioning
confidence: 65%
“…Then, the question arises why the core P, but not the KP, is capable of stimulating the G6PD transcription. A clue to solve this problem came from our recent finding that Insl possesses one and two pairs of DNase I hypersensitive sites in 1FH and 2512H, respectively, and that the sites map within the 0.6-kb core sequence in both mutants (Ito et al 1989). It is known that active or inducible genes are highly sensitive to digestion with DNase I and that the sensitive sites are localized in many cases at or near the 5' end of the genes and are associated with alteration of the chromatin structure.…”
Section: Factors Specifically Bound To the Core P Elementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Hairy-wing mutations, transposons within a structural gene cause an increased level of truncated transcripts (Campuzano et al, 1986). In three high-G6PD activity mutants (Ito et al, 1989) and the Om(1D) mutations (Tanda and Corces, 1991), overexpression of the gene product is caused by the activity of a nearby transposon. Although ourAdhl mutations were generated by a transposon, they differ from the Drosophila mutants by the fact that a transposon is no longer present at the locus.…”
Section: Discussionmentioning
confidence: 99%